Base-mediated alternate route for multi-functionalized allylbenzenes using ring transformation strategy. Issue 16 (17th August 2020) - Shetgaonkar, Samata E.; Singh, Fateh V.
Abstract: A simple yet innovative approach for the construction of multi-substituted allylbenzenes 14, 16 and 18 with 'donor-acceptor' functionalities has been delineated through base-mediated ring transformation of 6-aryl-2 H -pyran-2-ones 13, 15 and 17 respectively with commercially available 5-hexen-2-one 11 as carbanion source. The reactions were carried out at room temperature without using any catalyst or organometallic reagents with excellent functional group tolerance. Moreover, the present method is possible alternate route to access allylbenzenes apart from usual metal-catalyzed cross-coupling reactions. Graphical Abstract: